Aplasia cutis congenita - Yerram, Chinmai; Kilaru, Krishna Rajesh; Gogula, Anusha; Karunakar, Peram (International Journal of Research in Dermatology, 2019)
Aplasia cutis congenita (ACC) is a rare condition in which there is congenital focal absence of skin with or without absence of underlying structures such as bone. Consanguinity may play a role. The cause of this condition is unclear and appears to be multifactorial; contributory factors may include teratogens, genes, trauma and compromised blood flow to the skin. Various expressions of Adams Oliver syndrome (AOS) have also been reported which is a rare autosomal dominant congenital disorder characterized by absence of skin and or underlying structure over scalp along with transverse limb defect. It was first described by Adam and Oliver in 1945.